2019
DOI: 10.22159/ajpcr.2019.v12i6.33059
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Evaluation of Antimicrobial Activity in the Whole Plant Extracts of Gloriosa Superba

Abstract: Objectives: The aim of this research work was to carry out the phytochemical screening and to evaluate the antibacterial and antifungal activity of the whole plant extract (shoot, flower, and tuber) of the flame lily (Gloriosa superba). Materials and Methods: In the current work, phytochemicals were extracted from different parts of the plant using different solvents dimethyl sulfoxide, ethyl acetate, and ethanol (ETOH). These phytochemicals contained alkaloids, flavonoids, terpenoids, tannins, saponins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The resistance of Gram-negative bacteria is attributed to the character hydrophilic of the membrane that blocks the penetration of hydrophobic molecules such as polyphenols [29]. The bacterial wall of E. coli, for example, is very rich in lipopolysaccharides that prevent molecules hydrophobic to cross the membrane [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The resistance of Gram-negative bacteria is attributed to the character hydrophilic of the membrane that blocks the penetration of hydrophobic molecules such as polyphenols [29]. The bacterial wall of E. coli, for example, is very rich in lipopolysaccharides that prevent molecules hydrophobic to cross the membrane [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial properties of leaf and stem extract were also evaluated. Also, it was observed that the extract obtained from tubers exhibited noteworthy antimicrobial activity against S. aureus and E. coli (Chimahali et. al., 2019).…”
Section: Antibacterial and Antifungalmentioning
confidence: 99%
“…Anita et al [18] were studied the ethanolic tissue extract of Purpura bufo exhibited the maximum zone inhibition against S. aureus. Chimahali et al [19] were reported that the maximum zone inhibition when observed by S. aureus (19mm) using ethyl acetate tuber extract of Gloriosa superba. In earlier findings, the ethyl acetate extract of Marselia minuta was showed the more active toward S. aureus and P. aeruginosa [20].…”
Section: Antibacterial Activitymentioning
confidence: 99%